Which Imaging Tools are Best for CV Risk Assessment? - Jacobson, Anne (MD Conference Express, 2011)
Risk stratification tools are critical for classifying cardiovascular (CV) risk and guiding therapy, particularly in asymptomatic patients. In this session, experts discussed new data that support the use of noninvasive imaging modalities as adjuncts to traditional risk factors in CV risk assessment.